INTEGRATION OF ARTIFICIAL INTELLIGENCE IN ADAPTIVE LEARNING: OPPORTUNITIES AND CHALLENGES FOR TEACHERS IN THE ERA OF EDUCATION 5.0 - Manurung, Imelda Darmayanti (MSJ : Majority Science Journal, 2025)
Abstract The integration of Artificial Intelligence (AI) in adaptive learning represents a transformative shift in Indonesia’s basic and secondary education system, aligning with the vision of Education 5.0 that emphasizes human-centered and technology-empowered learning. AI-driven adaptive systems have demonstrated the ability to personalize learning pathways, automate formative assessment, and provide data-supported instructional recommendations that enhance student outcomes. This study employs a systematic literature review to analyze the opportunities and challenges facing Indonesian teachers in implementing adaptive AI at the K–12 level. Findings show that while AI enables differentiated instruction, timely remediation, and deeper learning engagement, successful adoption depends significantly on teachers’ digital pedagogical literacy, data-informed decision-making, and ethical understanding of algorithmic systems. Key challenges include unequal infrastructure, varying teacher readiness, privacy risks in student data management, and limited policy frameworks. The study concludes that AI should serve as a pedagogical partner rather than a replacement for teachers, reinforcing the irreplaceable role of educator empathy, socio-emotional support, and professional judgment. Strategic competence development, equitable digital access, and clear regulatory guidance are essential to ensure that AI integration strengthens educational equity and instructional quality within Indonesia’s Education 5.0 ecosystem.